Integrasi Nilai Transendental dalam Pembelajaran Abad ke-21: Studi Komparatif Kualitatif antara Kurikulum Pesantren dan Kurikulum Cambridge - Musleh; abdul wafi; Fahim Abu Ramadhan; Septiadi; Ahsan Hakim (Educational Research Center, 2025)
This study aims to explore the integration of transcendental values within the context of 21st-century learning through a qualitative comparative study between the pesantren curriculum and the Cambridge Curriculum. The research is grounded in the need to reconstruct the global educational paradigm to emphasize not only cognitive competence and 21st-century skills but also spiritual and moral dimensions as the foundation for holistic human character development. The study employs a qualitative approach based on library research and content analysis of curriculum documents, Islamic educational literature, and Cambridge Curriculum policy references. The findings reveal that the pesantren curriculum positions transcendental values as the epistemological core of the entire learning process, whereas the Cambridge Curriculum emphasizes rationality, learner autonomy, and assessment based on global competency achievements. The intersection of the two lies in universal values such as honesty, responsibility, and collaboration, which have high relevance to 21st-century education. Theoretically, this research proposes an integrative model that combines spiritual-transcendental dimensions with modern competency-based pedagogical principles. Practically, it provides a conceptual framework for developing holistic curricula in Islamic educational institutions that are globally oriented yet rooted in divine values.